Does intra-firm bargaining matter for business cycle dynamics? - Michael Krause; Thomas A. Lubik (Deutsche Bundesbank, 2007)
We analyse the implications of intra-firm bargaining for business cycle dynamics in models with large firms and search frictions. Intra-firm bargaining implies a feedback effect from the marginal revenue product to wage setting which leads firms to over-hire in order to reduce workers' bargaining position within the firm. The key to this effect are decreasing returns and/or downward-sloping demand. We show that equilibrium wages and employment are higher in steady state compared to a bargaining framework in which firms neglect this feedback. However, the effects of intra-firm bargaining on adjustment dynamics, volatility and comovement are negligible.
Keywords: E32; J64; E24; 330; Strategic wage setting; search and matching frictions; business cycle propagation; Konjunkturtheorie; Lohnverhandlungen; Allgemeines Gleichgewicht; Arbeitsuche; Matching; Theorie